1987
DOI: 10.1007/bf00192504
|View full text |Cite
|
Sign up to set email alerts
|

The gas-phase reaction of ClONO2 with hydrogen chloride

Abstract: The gas-phase reaction ofC1ONO 2 with HC1 was investigated using two large-volume environmental chambers with analysis by in situ long pathlength Fourier transform infrared absorption spectroscopy. In these chambers the reaction was observed to proceed, at least in part, by heterogeneous routes, and an upper limit to the rate constant for the homogeneous gas-phase reaction of k(C1ONO 2 + HC1) < 1.5 x 10 -t9 cm 3 molecule -~ s -1 was derived at 298-+ 2K. Assuming that this room-temperature upper limit to the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
3

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 22 publications
5
65
3
Order By: Relevance
“…75,[77][78][79]82,83 For the reactions of secondary alkyl peroxy radicals, RCH(OO • )R′, with NO, the alkyl nitrate yields at room temperature and atmospheric pressure of air increase with increasing carbon number 74,75,79,84 (see also the discussion of products below). On the basis of the small amount of data available, the alkyl nitrate yields from the reactions of NO with primary, RCH 2 O 2 • , and tertiary, RR′R′′CO 2 • , alkyl peroxy radicals appear to be lower than that for a secondary alkyl peroxy radical of the same carbon number.…”
Section: Reactions Of Organic Peroxy (Ro 2 • ) Radicalsmentioning
confidence: 96%
“…75,[77][78][79]82,83 For the reactions of secondary alkyl peroxy radicals, RCH(OO • )R′, with NO, the alkyl nitrate yields at room temperature and atmospheric pressure of air increase with increasing carbon number 74,75,79,84 (see also the discussion of products below). On the basis of the small amount of data available, the alkyl nitrate yields from the reactions of NO with primary, RCH 2 O 2 • , and tertiary, RR′R′′CO 2 • , alkyl peroxy radicals appear to be lower than that for a secondary alkyl peroxy radical of the same carbon number.…”
Section: Reactions Of Organic Peroxy (Ro 2 • ) Radicalsmentioning
confidence: 96%
“…) gave the plot of vs. C/A, with slope of the straight line (C/A) ϫ [NO] for k 7 the recommended value of Atkinson et al[16], the same value for all RO 2 radicals, k ϭ ments, each series differing by an interval of about one month, were made at 463 and ), and gave ten 473 K coupled values (k 3 , T) which are summarized inTable II.This isomerization rate constant k 3 (which is proportional to k 7 ) would change if the literature recommended value of k 7 were modified. The Arrhenius plot, was obtained from the data ofTable II.…”
mentioning
confidence: 99%
“…It is interesting to note that in contrast to the broad data base available for the kinetics of the reaction of OH radicals with many classes of organic compounds [3,41, there are relatively few studies reported for heterocyclic compounds. Thus, for example, the reaction of hydroxyl radicals with pyrrole has been the subject of only one previous study [5], using a relative rate technique at 295 K.…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanism of reactions (1) and (2) has been discussed recently by several workers [5][6][7]9]; for reaction (1) two likely mechanisms exist, either H-atom abstraction from the N-H bond or addition to the olefinic double bonds. By analogy with the reaction of OH with dimethylamine, H-atom abstraction from the N-H bond in pyrrole is expected to proceed via the initial formation of an addition complex followed by rapid decomposition leading to overall H-atom abstraction [41.…”
mentioning
confidence: 99%